The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/srep44392
|View full text |Cite
|
Sign up to set email alerts
|

Chemogenetic stimulation of the hypoglossal neurons improves upper airway patency

Abstract: Obstructive sleep apnea (OSA) is characterized by recurrent upper airway obstruction during sleep. OSA leads to high cardiovascular morbidity and mortality. The pathogenesis of OSA has been linked to a defect in neuromuscular control of the pharynx. There is no effective pharmacotherapy for OSA. The objective of this study was to determine whether upper airway patency can be improved using chemogenetic approach by deploying designer receptors exclusively activated by designer drug (DREADD) in the hypoglossal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 38 publications
(27 reference statements)
1
40
0
Order By: Relevance
“…Two previous studies used cre-dependent viral vectors to transduce hypoglossal motoneurons of ChAT-Cre+ mice with hM3Dq receptors 21,22 . Those studies identified that systemic administration of clozapine-N-oxide led to increased tongue muscle activity that enlarged the pharyngeal airspace in anesthetized mice 21 , and caused sustained tongue muscle activation across sleep-wake states in behaving mice 22 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two previous studies used cre-dependent viral vectors to transduce hypoglossal motoneurons of ChAT-Cre+ mice with hM3Dq receptors 21,22 . Those studies identified that systemic administration of clozapine-N-oxide led to increased tongue muscle activity that enlarged the pharyngeal airspace in anesthetized mice 21 , and caused sustained tongue muscle activation across sleep-wake states in behaving mice 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies used cre-dependent viral vectors to transduce hypoglossal motoneurons of ChAT-Cre+ mice with hM3Dq receptors 21,22 . Those studies identified that systemic administration of clozapine-N-oxide led to increased tongue muscle activity that enlarged the pharyngeal airspace in anesthetized mice 21 , and caused sustained tongue muscle activation across sleep-wake states in behaving mice 22 . However, a key limitation of such 'chemogenetic' studies 21,22 is the inability to impose acute, precise and direct control over hypoglossal motor activity using an intervention that can be transiently turned on and off, as well as graded in intensity, in order to interrogate properties of net motor excitability and responsivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Manipulation of certain potassium channels at the hypoglossal motor pool can activate the tongue musculature throughout sleep to waking levels 40, 42 . Importantly, it has been recently shown that introducing a “designer” receptor into the hypoglossal motor pool, and selectively modulating it with a “designer” drug, led to significant and sustained increases in tongue muscle activity and increases in upper airway size in pre-clinical rodent models 60, 61 . Moreover, the increases in tongue muscle activity during sleep persisted for 8–10 hours, were of physiological pattern and magnitude, and were specific and selective for the tongue with no effects on diaphragm or postural muscle activities, or sleep-wake states 60 .…”
Section: Mapping Potential Drug Targets In the Circuitry Controllimentioning
confidence: 99%